Solvent dependence of crystal structure and dielectric relaxation in ferromagnetic [MnCr(oxalate)] salt - Wu, Jia-bing; Huang, Rui-Kang; Takahashi, Kiyonori; Nakamura, Takayoshi (Dalton transactions : an international journal of inorganic chemistry, 2022)
[MnCr(oxalate) 3 ] − possesses a two-dimensional ferromagnetic network that is an ideal system for the construction of multifunctional molecular materials based on ferromagnetism. This is because additional functions, such as ferroelectricity, can be hybridised by incorporating functional cations between the layers. However, the majority of [MnCr(oxalate) 3 ] − networks readily incorporate solvent molecules upon crystallisation, and it is sometimes difficult to measure the crystal physical properties because of the collapse associated with desolvation. Upon desolvation, the polar crystal (CBA + )([18]crown-6)[MnCr(oxalate) 3 ] − (CH 3 OH) ( 1 ·CH 3 OH) (CBA + = 4-carboxybutan-1-aminium) underwent a crystal-to-crystal transformation to form (CBA + )([18]crown-6)[MnCr(oxalate) 3 ] − , 1 . Furthermore, this change was accompanied by hydrogen bond reorganisation in the (CBA + )([18]crown-6) supramolecular assembly. Both crystals exhibited ferromagnetic ordering at approximately 5 K. In crystal 1 , a "merry-go-round" motion of [18]crown-6 was observed, with an activation energy of 41.41 kJ mol −1 , which resulted in dielectric relaxation. This crystal-to-crystal structural transformation provides a strategy for designing multifunctional hybrid materials, in which an additional function arises from molecular motion. The orientation of (4-carboxybutan-1-aminium)([18]crown-6), as well as the rotational behaviour of [18]crown-6, is triggered by guest CH 3 OH through hydrogen bond reorganisation.